2017
DOI: 10.1098/rsos.171371
|View full text |Cite
|
Sign up to set email alerts
|

Tweeting birds: online mentions predict future citations in ornithology

Abstract: The rapid growth of online tools to communicate scientific research raises the important question of whether online attention is associated with citations in the scholarly literature. The Altmetric Attention Score (AAS) quantifies the attention received by a scientific publication on various online platforms including news, blogs and social media. It has been advanced as a rapid way of gauging the impact of a piece of research, both in terms of potential future scholarly citations and wider online engagement. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
40
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 35 publications
2
40
0
1
Order By: Relevance
“…These findings indicate the immediacy of altmetrics in identifying popular new research and, possibly, predicting future citations (Finch, OHanlon, & Dudley, 2017). It should be acknowledged that Altmetrics and other social media platforms are relatively new, and altmetrics scores, particularly those of older articles, need to be viewed with caution.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…These findings indicate the immediacy of altmetrics in identifying popular new research and, possibly, predicting future citations (Finch, OHanlon, & Dudley, 2017). It should be acknowledged that Altmetrics and other social media platforms are relatively new, and altmetrics scores, particularly those of older articles, need to be viewed with caution.…”
Section: Discussionmentioning
confidence: 80%
“…Similar findings were reported by other studies including those from orthodontics (Livas & Delli, ), and even a negative correlation between the publication date and online attention was reported by Zhou et al (). These findings indicate the immediacy of altmetrics in identifying popular new research and, possibly, predicting future citations (Finch, OHanlon, & Dudley, ). It should be acknowledged that Altmetrics and other social media platforms are relatively new, and altmetrics scores, particularly those of older articles, need to be viewed with caution.…”
Section: Discussionmentioning
confidence: 87%
“…These include the role of group level cooperation in acquiring resources, social learning, and the attainment of social status 37 . In line with these ideas, scientists with larger research networks gain more funding 44 and are more highly cited than scientists with fewer co-authors 29,4548 , while articles mentioned on social media gain more citations 49,50 , suggesting that sociality in science also promotes greater access to resources, knowledge of new research, and leads to higher status among scientific peers. In turn, funding and citation rates are both factors that positively influence career progression and longevity in science 51–54 .…”
Section: Introductionmentioning
confidence: 86%
“…Peoples et al found that Twitter can predict the citation rate of ecology articles, 1 and our own recent study used Altmetric data to show that not only did online mentions predict future citations in ornithology, but that Twitter contributed 75% of all the altmetrics of ornithology articles. 2 More recently, and more broadly, Ortega showed that papers in journals with their own Twitter accounts are tweeted up to 46% more than papers in journals without a Twitter account, and this activity translated to an up to 34% increase in citations of a journal's own articles. 3 The question I am frequently asked by nonornithologists is how did the (to many, obscure) field of ornithology achieve this?…”
mentioning
confidence: 99%
“…Twitter is by far the largest contributor to ornithology articles' altmetrics. Reproduced from Finch et al2 Like many small societies, our resources are very limited and come largely from our small membership and income from our journal. We are therefore very careful about where and on what we spend our finite resources.The digital age has allowed societies to reduce some costs with better use of online communication.…”
mentioning
confidence: 99%